(3QSGdI aj hba MeRI hgTGe Ydi GdJeGe hGdceGds - (3Ydj Hf YKeGf Hf eMeO Hf CMeO, CHh GdHbGA GdYPQj, hjYQa H (B: (3GHf GdbGUM,J (B801 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg hjcGaF eRjOg hHYO agPg eSGFd ai ePgH MeRI hgTGe UMJ ai GdfTQ hZjQg ef ZjQ Jhba hdG JVYja s
(3BNQgG (B:s
(3hcPdc eY GdeO hGdbUQ CjVkG agPg eSGFd MeRI hgTGe bS YdjgG eG hbY ef fXGFQgG abO HGdZJ ai JHjfgG QGLjkG KhGH Gddg JYGdi hgh MSHi hfYe Gdhcjd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf hGdahGJM HGdMeQIs
(3HBNQgG eWGdYI ai bQGAGJ dhQT hahGFO s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdbQGAGJ hGdJLhjOs